A AHLI WARIS PENGGANTI MERUSAK TATANAN HUKUM KEWARISAN ISLAM: Studi Kritis Terhadap Kompilasi Hukum Islam: Indonesia - Defel Fakhyadi (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
Substitute heirs are a form of renewal of Islamic law in Indonesia which is then sublimated in the statutory regulations contained in the Compilation of Islamic Law (KHI). The granting of inheritance rights to substitute heirs is the result of ijtihad which is influenced by the sociological conditions of Indonesian society which also has three inheritance law systems, namely civil inheritance BW, Islamic inheritance and customary inheritance. The concept of inheritance in Indonesia at the practical level influences each other considering that the three inheritance models are applied in Indonesia. This research will reveal the concept of inheritance of substitute heirs contained in KHI which is different from the concept of inheritance contained in fiqh books whose designation has been explained in detail qath’i in the text. This type of research is descriptive qualitative based on literature research with analysts data through a descriptive critical analysis approach resulting in a responsive understanding of Islamic inheritance law. This study concludes that the granting of inheritance rights to substitute heirs is a form of modernization of inheritance law in Indonesia by considering the benefit side but creates several legal consequences by making Islamic inheritance law a law that is zanni dilalah so that it can be ijtihad, causing legal uncertainty and undermining the legal order of Islamic inheritance which is the consensus of the ulama. Keywords: Substitute heirs, Islamic inheritance law, KHI Substitute heirs are a form of renewal of Islamic law in Indonesia which is then sublimated in the statutory regulations contained in the Compilation of Islamic Law (KHI). The granting of inheritance rights to substitute heirs is the result of ijtihad which is influenced by the sociological conditions of Indonesian society which also has three inheritance law systems, namely civil inheritance BW, Islamic inheritance and customary inheritance. The concept of inheritance in Indonesia at the practical level influences each other considering that the three inheritance models are applied in Indonesia. This research will reveal the concept of inheritance of substitute heirs contained in KHI which is different from the concept of inheritance contained in fiqh books whose designation has been explained in detail qath’i in the text. This type of research is descriptive qualitative based on literature research with analysts data through a descriptive critical analysis approach resulting in a responsive understanding of Islamic inheritance law. This study concludes that the granting of inheritance rights to substitute heirs is a form of modernization of inheritance law in Indonesia by considering the benefit side but creates several legal consequences by making Islamic inheritance law a law that is zanni dilalah so that it can be ijtihad, causing legal uncertainty and undermining the legal order of Islamic inheritance which is the consensus of the ulama. Keywords: Substitute heirs, Islamic inheritance law, KHI